EFEKTIVITAS SOSIALISASI DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DALAM MENGHADAPI PILKADA 2024 KOTA BENGKULU - Julita, Julita; Alfatah, Dhika; Faridah, Faridah (Jurnal STIA Bengkulu, 2025)
The purpose of this study was to determine the effectiveness of socialization in increasing community participation in facing the 2024 Pilkada in Bengkulu City. The sample in this study were the KPUD Commissioner, PPK Chairperson, PPK Members, PPS Chairperson, PPS Members and the Bengkulu City Community. Data collection methods with primary data and secondary data. Data analysis techniques with data reduction, data presentation and conclusions. The results of the study showed that. The results of the study obtained by the researcher were that with the socialization from the KPUD both from the KPU, PPK and PPS commissioners to all levels of society, where the socialization provided had material, presenters, systems (methods), targets, media time and place. With this socialization, the community participates in conducting general elections, public awareness of the importance of voting rights so that they exercise their voting rights by participating in voting according to their conscience, this proves that the socialization carried out in facing the regional elections has been effective where the effectiveness of the socialization of the general election commission can, , , candidate selection, voting for candidates and political parties, election dates, how to vote, candidates and political parties, invitations to increase public knowledge, understanding and awareness of the rights and obligations in the election of presenters, systems (methods), targets, media, time and place in socializing.